2017
DOI: 10.1080/00036846.2017.1321840
|View full text |Cite
|
Sign up to set email alerts
|

Does institutional quality resolve the Lucas Paradox?

Abstract: The Lucas Paradox observes that capital flows predominantly to relatively rich countries, contradicting the neoclassical prediction that it should flow to poorer capital-scarce countries. Alfaro, Kalemli-Ozcan, and Volosovych (2008) (AKV) argue that cross-country variation in institutional quality can fully explain the Paradox, contending that if institutional quality is included in regression models explaining international capital inflows, a country's level of economic development is no longer statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Human capital and the degree of openness to foreign countries (development of foreign trade) were recognized as relevant for encouraging higher investment flows to the host state as well. Significantly, none of those factors fully resolved the paradox (Akhtaruzzaman et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Human capital and the degree of openness to foreign countries (development of foreign trade) were recognized as relevant for encouraging higher investment flows to the host state as well. Significantly, none of those factors fully resolved the paradox (Akhtaruzzaman et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 94%
“…logCapflows is the log of average capital flows per capita per year, measured as the sum of foreign direct investment and portfolio equity flowing into a country in a particular year. In particular, the natural logs are taken to suppress outliers and endogeneity [26,44,45]. logGDP represents real gross domestic product per capita in the base year (2002), which is fixed to capture the Lucas Paradox.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of neoclassical economic theory, investments should occur in poorer economies if they are allowed to move freely, and this should continue to be true until investment returns are equalized in all countries [24][25][26]. However, Robert Lucas observed that evidence from reality stood contrary to what would be prescribed by neoclassical economic theory, wherein private capital did not actually flow into developing countries when comparing the state of capital inflows in the United States versus India.…”
Section: Implications Of the Lucas Paradox In Blended Financementioning
confidence: 99%
See 1 more Smart Citation
“…We focus on White's heteroscedasticity test since it is routinely used and reported in academic work on, for instance, agricultural economics (e.g., Bold et al, 2017), development economics (e.g., Hirvonen et al, 2017), innovation economics (e.g., Rojas et al, 2018;Stanko and Henard, 2017), …nancial economics (e.g., Bauer and Neuenkirch, 2017), …scal policy (e.g., Chen et al, 2017) or macro-economics (e.g., Atalla et al 2016;Montagnoli et al 2016). Over and above, in some cases, researchers start their empirical analysis by removing outliers and subsequently perform the White heteroscedasticity test -see, for instance, Akhtaruzzaman et al (2018), Ling and Wahab (2018), Carrera et al (2017) and Stanko and Henard (2017), amongst others. More generally, practitioners performing standard regression analysis are routinely confronted with the White test via built-in commands in statistical software packages such as Eviews, STATA or OxMetrics.…”
Section: Introductionmentioning
confidence: 99%